2016
DOI: 10.3906/bot-1602-11
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal and dark septate endophyte fungal associations in Asparagus

Abstract: We studied the arbuscular mycorrhizal (AM) and dark septate endophyte (DSE) fungal associations in five species of potgrown Asparagus (A. aethiopicus, A. densiflorus, A. setaceus, A. racemosus, and A. umbellatus). Root colonization by AM and DSE fungi and AM spore numbers in the soil were assessed. AM fungal diversity indices like species richness, Shannon-Weiner index, Simpson's index, evenness, and Jaccard's index were determined. Relationships among the fungal and soil variables were also examined. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Bueno de Mesquita et al (2018) suggested a role in mineralizing inorganic N, but the interactions between DSF and AMF remain uncertain. While some authors found positive interactions among them (Ranelli et al, 2015; Scervino et al, 2009; Thangavelu & Raji, 2016), others found that AMF and DSF responded differently to the same environmental factors (Bueno de Mesquita et al, 2018; Gooden et al, 2019; Huo et al, 2021; Jones & French, 2021). The different patterns of colonization may be attributed to the fact that AMF are obligate symbionts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bueno de Mesquita et al (2018) suggested a role in mineralizing inorganic N, but the interactions between DSF and AMF remain uncertain. While some authors found positive interactions among them (Ranelli et al, 2015; Scervino et al, 2009; Thangavelu & Raji, 2016), others found that AMF and DSF responded differently to the same environmental factors (Bueno de Mesquita et al, 2018; Gooden et al, 2019; Huo et al, 2021; Jones & French, 2021). The different patterns of colonization may be attributed to the fact that AMF are obligate symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as for AMF, DSF associations can either stimulate or reduce host plant growth (Caldwell et al, 2000). Also, the interactions between DSF and AMF were reported as positive (Ranelli et al, 2015; Thangavelu & Raji, 2016), negative (Bueno de Mesquita et al, 2018), and neutral (Huo et al, 2021; Seerangan & Thangavelu, 2014). In a recent review of microbial interactions in soils, Albornoz et al (2022) found that competition or facilitation among microbial groups largely depends on their mechanisms for carbon and nutrient acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the research is recent, and a more thorough understanding of the functionality of t his fungal group is still needed. Their coexistence with AMF has been reported in several plant groups (Nagaraj, Priyadharsini, & Muthukumar, 2015;Gucwa-Przepióra, Chmura, & Sokołowska, 2016;Thangavelu & Raji, 2016). Among the few studies on DSE in sugarcane, Nasim, Ali, Munawar, and Bajwa (2008) reported that 80% of the root samples were colonized by the DSE, suggesting that DSE have a role in the biocontrol of sugarcane diseases.…”
Section: Inoculation Treatmentsmentioning
confidence: 95%
“…Acta Scientiarum. Agronomy, v. 42, e42477, 2020 Several researchers have reported the simultaneous colonization of AMF and DSE in different plant species (Gucwa-Przepióra et al, 2016;Thangavelu & Raji, 2016). However, the functioning and importance of the triple interaction "DSE: AMF: plants" is not commonly studied; therefore, it is not fully understood (Debnath et al, 2015;Della Monica, Saparrat, Godeas, & Scervino, 2015).…”
Section: Inoculation Treatmentsmentioning
confidence: 99%
“…Most medicinal plants' roots and agronomic and vegetable crops exhibit endomycorrhizal association (Gaur and Kaushik 2011). Thangavelu and Raji (2016) Rhizophagus irregularis exhibited maximum AMF root colonization (43 ± 1.00%) in Ashwagandha, followed by Claroideoglomus claroideum (34 ± 4.33%). Root colonization by R. irregularis was greatest in marigolds (73 ± 2.88%).…”
Section: Root Colonizationmentioning
confidence: 99%